Testing the boundaries: Seasonal residency and inter-annual site fidelity of basking sharks in a proposed marine protected area - Doherty, PD; Baxter, JM; Godley, BJ; Graham, RT; Hall, G; Hall, J; Hawkes, LA; Henderson, SM; Johnson, L; Speedie, C; Witt, MJ (Biological Conservation, 2017)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. There is a growing need to understand the inter-annual movements of mobile marine species of conservation concern to inform the design and placement of Marine Protected Areas (MPAs) to maximise their conservation potential. We use satellite telemetry data from 36 basking sharks (Cetorhinus maximus) tracked in 2012, 2013 and 2014 (cumulative total: 1598 days; median: 44 days; range: 10–87 days) to quantify movements in coastal waters off the west coast of Scotland within the Sea of the Hebrides proposed MPA. Sharks exhibited seasonal residency to the proposed MPA, with a mean of 84% of filtered best daily locations occurring within its boundaries (2012 = 80%, 2013 = 90% and 2014 = 74%). Three long-term tracked basking sharks demonstrated inter-annual site fidelity, returning to the same coastal waters in the year following tag deployment, with two returning to within the boundaries of the proposed MPA. These data likely suggest the area experiences favourable conditions and/or resources for basking sharks across years and, if designated, coupled with appropriate management, could afford protection during summer months. This project was funded by Scottish Natural Heritage and the University of Exeter. We extend our sincere thanks to the skippers and crew of the Sula Crion and Bold Ranger of Sealife Surveys, Tobermory. The attachment of satellite transmitters was regulated by the UK HM Government Home Office under the Animals (Scientific Procedures) Act 1986 (Project Licence 30/2975) and under the Wildlife & Countryside Act 1981 (as amended) (License(s): 13904, 13937 and 13971). PD was supported by a NERC PhD studentship NELŁ501669\1.